Adaptive behavior in adolescents and adults with Down syndrome: Results from a 6‐month longitudinal study. Issue 1 (20th December 2018) - Spiridigliozzi, Gail A.; Goeldner, Celia; Edgin, Jamie; Hart, Sarah J.; Noeldeke, Jana; Squassante, Lisa; Visootsak, Jeannie; Heller, James H.; Khwaja, Omar; Kishnani, Priya S.; Liogier d'Ardhuy, Xavier
Abstract : Measures of adaptive behavior are important in the assessment and treatment of individuals with intellectual disabilities (ID). The purpose of the current study was to evaluate the stability of an established and a novel measure of adaptive behavior over time, and their suitability as outcome measures in clinical trials targeting individuals with Down syndrome (DS). This 6‐month, longitudinal, noninterventional, multinational study included adolescents (12–17 years) and adults (18–30 years) with DS. Participants were from seven countries (11 different sites) with English, Spanish and French as their native language. The Vineland Adaptive Behavior Scales‐II (VABS‐II) and a newly developed Clinician Global Impression (CGI) scale were administered at baseline, 1 and 6 months. Adults had lower composite standard scores on all domains of the VABS‐II compared with adolescents. The communication domain was a weakness relative to the socialization and daily living skills domains on the VABS‐II and the CGI‐Severity scale. These findings were stable over 6 months, as exhibited by high intraclass correlations (>0.75). These results provide valuable baseline data for use in trial design and endpoint selection for studies including individuals with DS. ClinicalTrials.gov identifier: NCT01580384.